A “Work of Life”: Jane Harrison on Older Age - Svare Valeur, Peter (Age, Culture, Humanities: An Interdisciplinary Journal, 2024)
The article examines the classical scholar Jane Ellen Harrison’s (1850-1928) thoughts about aging both as a cultural phenomenon and as personal experience. It argues that her reflections are poised between two diverging ideas about life which I term bergsonism and olympianism. While the former, according to Harrison, points to life as wholeness and permanent process (and which she illustrates by the figures of snowball and wheel, by the imperfective verb in the Russian novel, by the importance of ritual, or by her embracement of imbecility), the latter indicates detachment, idiocy, the perfect tense, discontinuity, and tragic vision. Of particular interest to the article are Harrison’s three later essays “Crabbed Age and Youth,” “Aspects, Aorists, and the Classical Tripos,” and “Reminiscences of a Student’s Life.” The article shows the variety of perspectives—anthropological, mythical, linguist, aesthetic, and philosophical—which Harrison makes use of to explain the phenomenon of aging.